India’s Union Budget 2023—Healthcare allocation leaves much to be desired - Vini Mehta; Varsha Thomas; Ankita Mathur (Journal of Family Medicine and Primary Care)
Healthcare is an imperative sector for India, considering the huge population in the country and the sub-par health facilities available to a majority of the country’s people. In this scenario, and given the havoc wreaked by the COVID-19 pandemic, owing to India’s lack of optimal healthcare infrastructure, a large part of the healthcare industry expected that India’s Union Budget 2023 would provide significant outlays for the sector. However, with the budgetary outlay for healthcare coming in at the 10th position from the top, this hope was severely dashed, leading to questions about the country’s interest in providing healthcare facilities to its people. This article discusses the various facets of the Union Budget, and the lack of focus on healthcare, while also delineating the reasons why budgetary focus on healthcare is imperative for a developing country like India. It has also brought forth potential solutions, such as a public–private partnership in healthcare, which could ensure increased access to healthcare, improved quality of healthcare, reduced costs, and enhanced innovation and research.